Morpho-molecular approach reveals a novel endophytic fungus, Scytalidium linderae sp. nov., associated with the roots of Lindera aggregata in China - Chen, Meng-Lan; Wu, Zi-Yang; Du, Yu-Jie; Du, Ru-Ping; Mukjang, Nilita; Luo, Xia (Phytotaxa, 2026)
Scytalidium species are widely distributed as pathogens, endophytes, saprobes, and parasites in plant tissues, decaying wood, soil, insect guts, and even on other fungi. During a survey of endophytic fungi associated with Lindera aggregata in Anhui Province, China, a novel species was isolated from healthy roots. It was identified as Scytalidium linderae sp. nov. based on its morphological characteristics and multi-locus phylogenetic analyses of ITS, LSU, SSU, and RPB2 sequences. Scytalidium linderae differs from other species in the genus by having arthroconidia that are oblong with truncate ends; they are hyaline to brownish-yellow and occasionally septate. Its chlamydospores are pyriform, doliiform, globose to subglobose, or oval, pale brown to brown, and occur singly or in chains. Detailed morphological descriptions, illustrations, and a phylogenetic tree are provided to confirm the identification of the new species. This study enhances our understanding of fungal taxonomy and the diversity of Scytalidium species associated with L. aggregata in China.